Implementing the school-wide autism competency model to improve outcomes for students on the autism spectrum: a multiple case study of three schools. Issue 8 (3rd July 2022) - Webster, Amanda; Roberts, Jacqueline
ABSTRACT: The rising number of students in schools identified as being on the autism spectrum has placed pressure on school leaders and staff to gain knowledge and take on new practice. A school-wide autism competency (SAC) approach utilises the research on elements of effective practice to build the capacity of school leaders and staff to create inclusive school cultures, implement evidence-based strategies, and improve outcomes for students on the autism spectrum. This paper reports on the experiences of three schools as they implemented the SAC approach in Queensland, Australia. A multiple case study design was utilised to examine the factors that influenced the implementation process and outcomes achieved at each school. Factors that influenced each school's ability to transform their practice for students on the autism spectrum included engagement of leaders, support from an external coach, involvement of parents, realignment of resources and staff, and the ability to manage change and competing priorities. Findings revealed that although all three schools increased staff's knowledge of students on the autism spectrum, the engagement and actions of leaders and the underlying culture of the school influenced the degree to which changes were implemented and outcomes were realised for students on the autism spectrum.